STUDI PENGEMBANGAN AGROINDUSTRI DAN AGROWISATA TERPADU DI DAERAH ALIRAN SUNGAI (DAS) KALI BEKASI KABUPATEN BOGOR - Djamudin, Anas Miftah Fauzi, Hadi Susilo Arifin, Sukardi TIP (Department of Agroindustrial Technology, Bogor Agricultural University, 2012)
Integrated agroindustry and agrotourism is an opportunity to develop the rural economics in Kali Bekasi watershed. The objective of this research was to develop a sustainable integrated system of agroindustry and agrotourism. The metodhs used for this study included analytical hierarchy process (AHP), Bayes method, and exponential comparison method (ECM). The results showed that top upstream watershed of Kali Bekasi was selected as the best location for the project. Five products of agroindustry, namely rice flour, tapioca, bamboo furniture, banana chips, and ground coffee were selected as the priority to be developed with three scenarios of tourist attractions, i.e: cultivation, harvesting/post-harvesting, and processing. Integration of the project was economically feasible with IRR of 31%, Net B/C of 1.95, and the total revenue from all tourist attractions of Rp 36, 905,000 per week. The weekly added values of agroindustry for each tourist attraction were Rp 11.760.000, Rp12.546.000, and Rp 12.563.000 respectively. The involvement of stakeholders including farmer associations, NGO, local youth organization (Karang Taruna), financing institution, SMEs, and local government is essentially required to implement this project with a community-based development approach.Keywords: agroindustry, agrotourism, watershed, AHP, Bayes method, MPE